The Effectiveness of Mental Health Literacy Enhancement Program on Awareness in Prevention of Risk Factors for Stress and Depression Among Adolescents in Dusit District, Bangkok Metropolis - Chaiyalap, Suteekarn; Vongareesawat, Chantrarat; Rujipairoch, Pornprom; Tupanich, Walaya; Wattanawikan, Nattanan (Vajira Nursing Journal, 2024)
This study aimed to evaluate the effectiveness of a mental health literacy enhancement program on raising awareness of risk factor prevention for stress and depression among student in urban areas of Bangkok. The concepts of mental health literacy and awareness were applied to the program development. The research took a quasi-experimental approach with a two group pre-posttest design. The sample consisted of 70 senior high school students in Dusit District, Bangkok, who were divided equally into experimental and control groups of 35 participants each. The data collection instruments included a general information record, a mental health literacy questionnaire, and a stress and depression a risk prevention awareness questionnaire. The study was conducted over four weeks, with data collected at week 1 and week 4. Data analysis was performed using descriptive statistics, paired t-tests, and independent t-tests. The research revealed the following: 1) at posttest, the experimental group exhibited higher mean score for mental health literacy and awareness than at pretest (p-value>.05) 2) at posttest, the experimental group demonstrated a statistically significant higher mean score for mental health literacy and awareness than the control group, but without statistical significance. Therefore, the mental health literacy the mental health literacy promotion program can increase students literacy and awareness about prevention risk factors for stress and depression better than self-learning from a brochure combined with receiving advice on mental health promotion.